Hydromulch Application to Bare Soil: Soil Temperature Dynamics and Evaporative Fluxes. Issue 1 (1st May 2018) - O'Brien, Peter L.; Acharya, Umesh; Alghamdi, Rashad; Niaghi, Ali Rashid; Sanyal, Debankur; Wirtz, Jeremy; Daigh, Aaron L. M.; DeSutter, Thomas M.
Abstract : Core Ideas: Hydromulch was applied to disturbed, bare soil at two rates. Micro‐Bowen ratio systems quantified soil temperature and evaporation. Hydromulch moderated temperature fluctuations, especially daily maximums. Hydromulch application reduced evaporation following rainfall. North Dakota State Univ., Dep. of Soil Science, Fargo, ND 58108. Soil disturbance reduces plant‐residue cover and can leave bare soil susceptible to erosion, extreme temperature fluctuations, and increased evaporation. Under such conditions, establishing vegetation is difficult. To overcome these difficulties, managing disturbed lands by applying surface cover may be a good step toward soil reclamation. Hydromulch is often applied to stabilize soil after disturbance, but its influence on soil temperature and evaporation has not been described. This study assessed soil temperature over time and used the surface energy balance to quantify evaporation from bare soil (0×), and two rates of hydromulch application, 1× and 3× (by weight) of manufacturer's recommended rate. Diurnal temperature extremes were highest in the 0× and least in the 3×. Evaporation was highest in the 0× during the final 18 d of data collection and lowest in the 3×. These findings indicate that temperature fluctuations decrease and evaporation is reduced when hydromulch is applied to bare soil, suggesting it may aid in soil reclamation.